Effects of a 2‐Year School‐Based Intervention of Enhanced Physical Education in the Primary School. (23rd July 2013) - Sacchetti, Rossella; Ceciliani, Andrea; Garulli, Andrea; Dallolio, Laura; Beltrami, Patrizia; Leoni, Erica
ABSTRACT: Background : This study aimed to assess whether a school‐based physical education intervention was effective in improving physical abilities and influencing daily physical activity habits in primary school children. The possible effect on body mass index (BMI) was also considered. Methods : Twenty‐six 3rd‐grade classes were randomly selected stratifying by geographic location (city, plain, hills) and were assigned either to an intervention (127 boys; 120 girls) or to a traditional (129 boys; 121 girls) physical education program. At baseline (age: 8‐9 years) and after a 2‐year follow‐up (age: 10‐11 years), information was collected about sport participation and daily activity habits using a self‐administered questionnaire. Height, weight, and BMI were measured and physical performance was assessed by means of standardized tests. Results : The enhanced program of physical education was effective in improving physical abilities of children and determining a decrease (boys: 10%; girls: 12%) in daily sedentary activities (preintervention versus postintervention, p < .05; intervention versus control group, p < .01). The percentages of overweight and obese children did not vary significantly, but the experimental group showed a significantly lower rise in BMI compared to the control group (p < .001). Conclusion : The school proved to be an ideal setting for promoting physical activity and achieving the required daily activity levels.